Regulation of cochlear hair cell function by intracellular calcium stores - Sinha, Ghanshyam P.; Frolenkov, Gregory I. (Frontiers in Cellular Neuroscience, 2024)
Mammalian hearing depends on the dual mechanosensory and motor functions of cochlear hair cells. Both these functions may be regulated by Ca 2+ release from intracellular stores. However, it is still unclear how exactly intracellular Ca 2+ release may affect either hair cell mechano-electrical transduction (MET) or prestin-dependent electromotility in outer hair cells (OHCs). Here, we used photo-activatable (caged) compounds to generate fast increases of either Ca 2+ or inositol-3-phosphate (IP3) in the cytosol of young postnatal rodent auditory hair cells, thereby stimulating either Ca 2+ -or IP3-induced releases of Ca 2+ from intracellular stores. Ca 2+ uncaging at the OHC apex initiated Ca 2+ wave propagating to the base of the cell with subsequent Ca 2+ build-up there. Ca 2+ uncaging at the OHC base generated long-lasting and apparently self-sustained Ca 2+ responses, further confirming Ca 2+ -induced Ca 2+ release in the OHC basal region. Photoactivated IP3 initiated a slow increase of cytosolic Ca 2+ ([Ca 2+ ]i) throughout the whole OHC, confirming the presence of slow-activated IP3gated Ca 2+ stores in OHCs. Interestingly, Ca 2+ uncaging produced no effects on OHC voltagedependent capacitance, a known electrical correlate of prestin-based electromotility. In an OHC, the rise of [Ca 2+ ]i is known to decrease axial stiffness of the cell and may modulate the stiffness of mechanosensory stereocilia bundles. To separate these two phenomena, we explored the potential effects of intracellular Ca 2+ release on mechanical properties of stereocilia bundles in cochlear inner hair cells (IHCs). Ca 2+ uncaging at the apex of an IHC caused a long-lasting increase in mechanical stiffness of stereocilia bundle without any changes in the amplitude or deflection sensitivity of the MET current. Thus, the regulation of hair bundle stiffness is the most likely physiological role IP3gated Ca 2+ release at the apex of the cell. In contrast, Ca 2+ -induced Ca 2+ release at the base of OHCs seems to regulate axial stiffness of the cells and its hyperpolarization in response to efferent stimuli.